2021
DOI: 10.1016/j.jsurg.2020.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Stress and the Surgical Resident in the COVID-19 Pandemic

Abstract: free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with rights for unrestricted research re-use and analyses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 22 publications
2
91
2
3
Order By: Relevance
“…All of the 52 neurosurgery trainees participating in an international survey reported that their social life had been affected by the pandemic [ 36 ]. Two studies reported that trainees were concerned about the health of their loved ones or transmitting the virus to them [ 30 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…All of the 52 neurosurgery trainees participating in an international survey reported that their social life had been affected by the pandemic [ 36 ]. Two studies reported that trainees were concerned about the health of their loved ones or transmitting the virus to them [ 30 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most common psychological symptoms measured with surveys or validated questionnaires reported included anxiety ( n = 103), depression ( n = 73), stress ( n = 68), fear ( n = 61), burnout ( n = 25), mental distress/health ( n = 21), and post-traumatic stress disorder (PTSD) ( n = 14) (Additional File 3 ). Most COVID-19 studies reported on physicians from USA ( n = 23) [ 41 , 52 , 66 , 70 , 77 , 90 – 107 ], China ( n = 22) [ 15 , 49 , 54 56 , 65 , 68 , 73 , 86 , 89 , 102 , 108 118 ] followed by India ( n = 21) [ 40 , 50 , 58 , 63 , 67 , 71 , 102 , 119 – 132 ] [ 41 , 52 , 66 , 70 , 77 ], Italy ( n = 10) [ 32 , 94 , 102 , 125 , 133 138 ], and Turkey ( n = 11) [ 35 , 44 , 94 , 139 – 146 ] [ 28 , 30 , 32 , 34 , 36 , 37 , 42 , 45 , 47 , 48 , 59 , 60 , 62 , 80 , 87 ]. .Sixtee...…”
Section: Resultsmentioning
confidence: 99%
“…One of the greatest concerns of the respondents (n = 73; response rate-73.7%) was the decline in operative exposure. Another significant finding of this research is that residents are more worried and concerned about the health of their loved ones than about their own risk and exposure of contracting COVID-19 [9].…”
Section: Critical Literature Reviewmentioning
confidence: 85%